Democracy. Discussions in Chilean Philosophy [Democracia. Discusiones en la Filosofía Chilena] - Friz-Echeverria, C (Universidad del Zulia, 2019)
This article adresses democracy problem, as it has been thought by a group of Chilean philosophers, in relation to military dictatorship, transition to democracy and post-authoritarian democracy s consolidation.We expone their critic to post-authoritarian democracy and its theoretical sustenance: the elitarian democratic theories and the consociative model. We also present the authors s democracy concept: This concept defends normative dimension of politics, the multidimensionality of democracy and participation. Finally, we reflect on authors contributions to think on an alternative democratic order. © 2019, Universidad del Zulia. All rights reserved.